2020
DOI: 10.1507/endocrj.ej19-0523
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gross extrathyroidal extension into major neck structures on the prognosis of papillary thyroid carcinoma according to the American Joint Committee on Cancer eighth edition

Abstract: This study investigated the impact of gross extrathyroidal extension into major neck structures on the prognosis of papillary thyroid carcinoma according to changes in the American Joint Committee on Cancer (AJCC)/Tumor-Node-Metastasis staging system. Overall, 183 patients with gross extrathyroidal extension into major neck structures were enrolled. The 10-year disease-specific survival (DSS) of patients in each stage showed appropriate correlation and stratification with the AJCC eighth edition. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…On the other hand, research on T4a tumors has shown that extensive ETE into adjacent organs is a significant predictor of poor prognosis ( 50 ). Our work has given supportive evidence that any extension into adjacent organs could substantially impair patient prognosis, which coordinated with other research that major neck structure invasion leads to early distant and locoregional recurrence ( 51 ). Although papillary thyroid microcarcinoma (PTMC) was considered to be less aggressive, extension to adjacent organs would still worsen the clinical survival of PTMC patients in our study and also indicated in other studies ( 8 , 52 – 55 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, research on T4a tumors has shown that extensive ETE into adjacent organs is a significant predictor of poor prognosis ( 50 ). Our work has given supportive evidence that any extension into adjacent organs could substantially impair patient prognosis, which coordinated with other research that major neck structure invasion leads to early distant and locoregional recurrence ( 51 ). Although papillary thyroid microcarcinoma (PTMC) was considered to be less aggressive, extension to adjacent organs would still worsen the clinical survival of PTMC patients in our study and also indicated in other studies ( 8 , 52 – 55 ).…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, research on T4a tumors has shown that extensive ETE into adjacent organs is a significant predictor of poor prognosis (50). Our work has given supportive evidence that any extension into adjacent organs could substantially impair patient prognosis, which coordinated with other research that major neck structure invasion leads to early distant and locoregional recurrence (51).…”
Section: A B D Csupporting
confidence: 80%
“…Thyroidectomy with modified radical neck dissection is recommended for N1b patients with gross ETE (1,4). Those unfavorable events have been shown to correlate to poor prognosis of patients with thyroid carcinoma, evidenced by increasing recurrence rate at both resection site and regional lymph node, lowering the overall and disease-free survival (5)(6)(7)(8)(9). Accordingly, the influence of nodule size on the risks of those unfavorable events should be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used method for evaluating TC survival clinically is the American Joint Committee on Cancer (AJCC) TNM staging, which divides TC invasion of different surrounding organs into different T stages from the perspective of the primary focus, such as dividing TC invasion of the laryngeal recurrent nerve, trachea, esophagus, or subcutaneous soft tissues into the T4a stage, and invasion of the prevertebral fascia or encircling the carotid artery or superior mediastinal vessels is classified as T4b stage [ 5 ]. Stage T4a and T4b patients aged <55 years were stage I, with a 10-year cancer-specific survival (CSS) of 97 %–100 %, whereas stage T4a patients aged >55 years were stage III, and stage T4b patients were stage IVA, with a 10-year CSS of 70 %–80 % and 48.5 %–60 %, respectively [ 6 ]. It is worth noting that the TNM staging included only tumor diameter, presence or absence of extrathyroidal extension (ETE), lymph node metastasis (LNM) and DM, it did not include patient gender, marital status, specific ETE site, multifocal nature, specific histopathological type, detailed surgical scope, and other treatment details.…”
Section: Introductionmentioning
confidence: 99%